A new freshwater gobiid species of Rhinogobius Gill, 1859 (Teleostei: Gobiidae) from the hillstream of Julongjiang basin, Fujian Province, southeastern China - Chen, I-Shiung; Wang, Shen-Chih (Zootaxa, 2025)
A new species of freshwater gobiid fish of genus Rhinogobius Gill, 1859, was collected from the Julongjiang basin, southern region of Fujian Province, China. Rhinogobius sexistriatus sp. nov. can be well distinguished from other congeners by their specific patterns of coloration and meristic features: (1) fins rays: second dorsal fin rays I/8; anal fin rays I/7; pectoral fin rays 17; (2) squamation: longitudinal scale series 26–28 (modally 27); perdorsal scales 4–5 (modally 5); (3) vertebral count 27; and (4) specific colouration: cheek with six parallel black stripes on lower side in male. Branchiostegal membrane light blue and spotless in male. First dorsal fin bright orange on more than 1/2 dorsal region in male. Second dorsal fin brownish yellow with 3 longitudinal rows of brown spots and a distal yellow margin in male. Pectoral fin base greyish with a large, wide oblique black mark and an orange spot behind in male. Caudal fin greyish with 5 vertical rows of brown spots in male. A diagnostic key to all valid species from Fujian Province, China is also provided in this paper.